KEADILAN DALAM PUTUSAN MA NO. 61P/HUM/2017 TERKAIT UJI MATERIIL ATAS PERATURAN BANK INDONESIA TENTANG UANG ELEKTRONIK - NIM. A1012211071, NAMIRA ZAKIA ANDJANI (Fakultas Hukum Universitas Tanjungpura, 2025)
AbstractThis research discusses justice in the Supreme Court (MA) Decision No. 61P/HUM/2017 regarding the judicial review of Bank Indonesia Regulation (PBI) No. 16/8/PBI/2014 on electronic money. The judicial review was filed by parties who believed that the regulation contradicted the Currency Law, particularly concerning the mandatory use of the Indonesian Rupiah for transactions within the country. This study aims to analyze how the Supreme Court